Gender and impact of climate change adaptation on soybean farmers' revenue in rural Togo, west Africa - Ali, E.; Awade, N.E.; Abdoulaye, Tahirou (Informa UK Limited, 2020)
This study assesses the impact of climate change (CC) adaptation on farm-level revenue among 500 soybean farmers randomly selected in three districts in Togo using endogenous switching regression method. The survey results indicate that only 40.37% of the women have adapted to CC against 59.62% of the men. Moreover, being member of farmer-based organization (FBO), access to credit and extension services, agricultural training of women are the main factors that increase the likelihood of adaptation. The gender-differentiated impact shows that women would earn more than men from adaptation, while losing compared to men if they do not take any adaptation actions. The loss from non-adapting to CC will increase by 0.268% of the soybean revenue. However, the heterogeneity effects suggest further assessment on the adopted technology in soybean farming in the study areas. Adaptation policy that seeks to ensure food security and enhance farmers’ welfare in subsistence agriculture should consider the gender dimension, while reviewing the financial policy in terms of affordability, access of extension services and supporting FBO will increase technologies adoption and farming revenue.